Low-grade renal carcinoma with histologic features overlapping with renal angiomyoadenomatous tumor and featuring polysomy 7 and 17 and a mutation in the von Hippel-Lindau gene: Report of a hybrid tumor and a few comments on renal angiomyoadenomatous tumor and papillary renal tumors with clear cells - Petersson, F. (2016)
10.1016/j.anndiagpath.2010.10.005